2003
DOI: 10.1093/molbev/msg022
|View full text |Cite
|
Sign up to set email alerts
|

G+C3 Structuring Along the Genome: A Common Feature in Prokaryotes

Abstract: The heterogeneity of gene nucleotide content in prokaryotic genomes is commonly interpreted as the result of three main phenomena: (1) genes undergo different selection pressures both during and after translation (affecting codon and amino acid choice); (2) genes undergo different mutational pressure whether they are on the leading or lagging strand; and (3) genes may have different phylogenetic origins as a result of lateral transfers. However, this view neglects the necessity of organizing genetic informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 68 publications
2
45
2
Order By: Relevance
“…In fact, the rightmost and leftmost parts of the plots that correspond to the ori do not display synteny, suggesting that such regions are subject to a higher rate of reshuffling or an increased acquisition of alien DNA by horizontal gene transfer (HGT) compared with the alignment within the B. longum phylogenetic group. Such findings contrast with what has previously been described for bacterial genome evolution, where it was suggested that the regions around the replication terminus display an increased frequency of HGT compared with the remainder of the chromosome (Daubin & Perriere, 2003).…”
Section: Resultscontrasting
confidence: 99%
“…In fact, the rightmost and leftmost parts of the plots that correspond to the ori do not display synteny, suggesting that such regions are subject to a higher rate of reshuffling or an increased acquisition of alien DNA by horizontal gene transfer (HGT) compared with the alignment within the B. longum phylogenetic group. Such findings contrast with what has previously been described for bacterial genome evolution, where it was suggested that the regions around the replication terminus display an increased frequency of HGT compared with the remainder of the chromosome (Daubin & Perriere, 2003).…”
Section: Resultscontrasting
confidence: 99%
“…The leftmost and rightmost parts of the plots that correspond to the ori region have no clear regions of synteny, which may indicate that these regions are subject to a greater rate of change by a higher rate of reshuffling or by an increased acquisition of foreign DNA by horizontal gene transfer. This contrasts with previous analyses of other bacteria (Daubin & Perriere, 2003), which suggested that the region opposite to the replication origin (terminus) had a higher frequency of phage insertion and 'orphan' gene acquisition. Other important regions with a null synteny correspond to the megaplasmid pMP118 and a large region next to the origin of replication at the end of the L. plantarum circular chromosome as depicted in Fig.…”
Section: General Genome Characteristicscontrasting
confidence: 99%
“…This is also correlated with several evolutionary features ( Figure 1): in many genomes, genes near the terminus of replication tend to have lower content in G + C nucleotides and to exhibit higher rates of evolution [12]. Also, as a result of the replication process, genes located close to the Ori can be significantly amplified in dividing cells, in comparison with those closer to the terminus.…”
Section: Glossarymentioning
confidence: 86%